Dorsetshire Labourers' Centenary Celebrations, 1934 (1934)
1934 1918-1939 "Dorsetshire Labourers' Centenary Celebrations, 1934" [T0316.jpg], 1934 Between August 25-September 2, 1934, the TUC organised a series of musical, dramatic and sports events in Dorset to mark the Centenary of the arrest and transportation of the Tolpuddle Martyrs. The TUC also issued an illustrated history of the event of 1834 and a souvenir badge and medallion. The TUC erected more permanent memorials by building 6 cottages for retired agricultural workers, raising a headstone (designed by Eric Gill) over James Hammett's grave and placing a plaque on Thomas Standfields cottage, where the Martyrs' union meetings took place